2006
DOI: 10.1016/j.jacc.2005.12.074
|View full text |Cite
|
Sign up to set email alerts
|

Pacing-Induced Increase in QT Dispersion Predicts Sudden Cardiac Death Following Cardiac Resynchronization Therapy

Abstract: The MAE in patients with BiVP are related to pacing-induced increases in QTD. Measures of ventricular repolarization at the time of pacemaker implantation may guide selection of patients for combined CRT and defibrillator therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 20 publications
(19 reference statements)
0
39
1
Order By: Relevance
“…In a study of 75 patients undergoing CRT, variation in QT dispersion before and after implantation was an independent predictor of major arrhythmic events; in a follow-up of 807 days, in the group with increased QT dispersion the incidence of events was 29%, while in those in whom it decreased, the incidence was 3% (p=0.0017). 30 The same study 30 assessed the interval between the peak and the end of the T wave (T peak-end ), another marker of dispersion of repolarization. Patients who suffered arrhythmic events during follow-up had a significantly smaller reduction in T peak-end than those who were event-free (−1.5±12.8 ms vs. −20.0±5.4 ms, p=0.047).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 75 patients undergoing CRT, variation in QT dispersion before and after implantation was an independent predictor of major arrhythmic events; in a follow-up of 807 days, in the group with increased QT dispersion the incidence of events was 29%, while in those in whom it decreased, the incidence was 3% (p=0.0017). 30 The same study 30 assessed the interval between the peak and the end of the T wave (T peak-end ), another marker of dispersion of repolarization. Patients who suffered arrhythmic events during follow-up had a significantly smaller reduction in T peak-end than those who were event-free (−1.5±12.8 ms vs. −20.0±5.4 ms, p=0.047).…”
Section: Discussionmentioning
confidence: 99%
“…Chalil et al [17] examined retrospectively the prognostic value of these parameters in predicting sudden cardiac death in CRT patients. Like our study they reported that increase in QT dispersion was the independent predictor of sudden cardiac death.…”
Section: Discussionmentioning
confidence: 99%
“…Recent publications have reported that repolarization abnormalities play a role in arrhythmogenesis (32,33). In this context, analysis of the duration of wave intervals in electrocardiograms (ECG) could potentially identify patients at risk for cardiac death and sudden cardiac death.…”
Section: Introductionmentioning
confidence: 99%